Temporal changes in survival in men with de novo metastatic prostate cancer: nationwide population-based study. (2nd January 2020) - Westerberg, Marcus; Franck Lissbrant, Ingela; Damber, Jan Erik; Robinson, David; Garmo, Hans; Stattin, Pär
Abstract: Background: There have been large changes in the pattern of detection, work-up and treatment of men with prostate cancer during the last two decades. Therefore, we aimed to investigate temporal changes in survival in men with metastatic prostate cancer. Methods: Population-based cohort study in Prostate Cancer data Base Sweden of 13, 709 men with de novo metastatic prostate cancer diagnosed between 1998 and 2015. Overall survival in four calendar periods were compared by the use of Kaplan–Meier analyses and Cox regression models including age at diagnosis, T stage and serum levels of prostate-specific antigen (PSA). Results: Between 1998–2001 and 2010–2015, median survival increased with 6 months for all men. The largest increase in survival was 14 months in men age 60–69 at diagnosis and in multivariable analysis risk of death decreased for men diagnosed in 2010–2015 compared to 1998–2001, hazard ratio (HR) 0.77 (95% CI: 0.68–0.86). The median PSA at date of diagnosis decreased with 46% from 181 ng/mL in 1998 to 98 ng/mL in 2015. Conclusions: There was an increase in survival among men with de novo metastatic prostate cancer in Sweden between 1998 and 2015. This increase was due to a decreased cancer extent indicated by lower PSA levels with ensuing longer lead times and speculatively also due to an increased use of chemotherapy in the latest time period. Given the increasing use of systemic treatment for advanced prostate cancer, our results are likely heralding larger increases in survival in men with metastatic prostate cancer in the near future.